Private Higher Education in Egypt: From Necessary Evil to Celebrated Player - Barsoum, Ghada (International Higher Education, 2022)
This article looks at the evolution of the role of private higher education institutions in Egypt, where the higher education landscape has been predominantly public. Until the early 1990s, private institutions had a very shy presence, primarily as a last resort for underachievers. They have shifted roles to become celebrated players tasked with the mission of improving the quality and competitiveness of the higher education system.